2014
DOI: 10.1007/s12307-014-0156-4
|View full text |Cite
|
Sign up to set email alerts
|

Angiotropism, Pericytic Mimicry and Extravascular Migratory Metastasis in Melanoma: An Alternative to Intravascular Cancer Dissemination

Abstract: For more than 15 years, angiotropism in melanoma has been emphasized as a marker of extravascular migration of tumor cells along the abluminal vascular surface, unveiling an alternative mechanism of tumor spread distinct from intravascular dissemination. This mechanism has been termed extravascular migratory metastasis (EVMM). During EVMM, angiotropic tumor cells migrate in a 'pericytic-like' manner (pericytic mimicry) along the external surfaces of vascular channels, without intravasation. Through this pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 75 publications
(91 reference statements)
3
76
0
Order By: Relevance
“…An increasing amount of evidence generated using intravital microscopy reveals that migration tracks are not created solely by matrix remodelling but also occur naturally in healthy tissues 6,11 . Examples include tracks along ECM fibres in the interstitial space 7,9,11 , between muscle and nerve fibres 11 , along or within blood vessels 23,24 and in the vasculature of target organs 25,26 . The different forms of migration tracks are illustrated schematically in FIG.…”
Section: Cell Confinement In Vivomentioning
confidence: 99%
“…An increasing amount of evidence generated using intravital microscopy reveals that migration tracks are not created solely by matrix remodelling but also occur naturally in healthy tissues 6,11 . Examples include tracks along ECM fibres in the interstitial space 7,9,11 , between muscle and nerve fibres 11 , along or within blood vessels 23,24 and in the vasculature of target organs 25,26 . The different forms of migration tracks are illustrated schematically in FIG.…”
Section: Cell Confinement In Vivomentioning
confidence: 99%
“…[53][54][55][56][57] It has been hypothesized that the interaction of melanoma cells with the abluminal vascular surface recapitulates embryonic migration of neural crest cells through pericyte mimicry. [58][59][60] Prior studies have shown that neural crest cells migrate along the external surface of microvascular channels during embryogenesis. 61,62 Interestingly, angiotropism has been identified in many congenital nevi, suggesting that EVMM may be an important mechanism for the development of these benign melanocytic lesions.…”
Section: Extravascular Migratory Metastasis and Angiotropismmentioning
confidence: 99%
“…Angiotropic tumour cells can spread along the abluminal surfaces of vessels without entering the vascular channels (intravasation), therefore making use of the blood vascular network as a track . As mentioned earlier, this tumour cell migration has been termed EVMM and is believed to represent a mechanism of tumour spread independent of intravasation and haematogenous dissemination .…”
Section: Introductionmentioning
confidence: 99%